A Timely Call to Arms: COVID-19, the Circadian Clock, and Critical Care. Issue 1 (February 2021) - Haspel, Jeffrey; Kim, Minjee; Zee, Phyllis; Schwarzmeier, Tanja; Montagnese, Sara; Panda, Satchidananda; Albani, Adriana; Merrow, Martha
We currently find ourselves in the midst of a global coronavirus disease 2019 (COVID-19) pandemic, caused by the highly infectious novel coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Here, we discuss aspects of SARS-CoV-2 biology and pathology and how these might interact with the circadian clock of the host. We further focus on the severe manifestation of the illness, leading to hospitalization in an intensive care unit. The most common severe complications of COVID-19 relate to clock-regulated human physiology. We speculate on how the pandemic might be used to gain insights on the circadian clock but, more importantly, on how knowledge of the circadian clock might be used to mitigate the disease expression and the clinical course of COVID-19.